Therapeutic Potential of Targeting the PERK Signaling Pathway in Ischemic Stroke - Xinyuan Yu; Lihong Dang; Ran Zhang; Wei Yang (MDPI AG, 2024)
Many pathologic states can lead to the accumulation of unfolded/misfolded proteins in cells. This causes endoplasmic reticulum (ER) stress and triggers the unfolded protein response (UPR), which encompasses three main adaptive branches. One of these UPR branches is mediated by protein kinase RNA-like ER kinase (PERK), an ER stress sensor. The primary consequence of PERK activation is the suppression of global protein synthesis, which reduces ER workload and facilitates the recovery of ER function. Ischemic stroke induces ER stress and activates the UPR. Studies have demonstrated the involvement of the PERK pathway in stroke pathophysiology; however, its role in stroke outcomes requires further clarification. Importantly, considering mounting evidence that supports the therapeutic potential of the PERK pathway in aging-related cognitive decline and neurodegenerative diseases, this pathway may represent a promising therapeutic target in stroke. Therefore, in this review, our aim is to discuss the current understanding of PERK in ischemic stroke, and to summarize pharmacologic tools for translational stroke research that targets PERK and its associated pathways.